Study of indigenous and non-indigenous practices for disease resistance in Capsicum: A review - Shahida, K; Mohammad, M K; Waqar, A; Ali, M; Mekhled, M A; Mohammad, H S (Plant Science Today, 2026)
Chilli pepper is a major cash crop in many countries, making a substantial contribution to export markets and national Gross Domestic Product (GDP). The production and quality of chilli peppers is significantly affected by biotic and abiotic stresses, particularly diseases caused by fungal, bacterial and viral pathogens. This review focuses on the major diseases such as anthracnose, root rot, powdery mildew and Fusarium wilt that led to substantial crop losses every year. Both traditional and contemporary non-indigenous strategies for inducing disease resistance have been discussed. The article maps key practices including the adoption of proper cultural practices, use of algal extracts and raising of disease-resistant varieties, application of biological and chemical control methods aimed at enhancing disease resistance in chilli. Relevant case studies are included to assess and support the effectiveness of agricultural practices that have proven effective in reducing crop losses and improving yield quality. The economic implications of improved disease resistance for tropical regions have also been discussed. Key recommendations are provided for policymakers, farmers and exporters and the need for technical and financial support as well as modern processing facilities to meet international market demands is emphasized. Further studies are required especially from the tropical areas where chilli consumption and cultivation are increasing. Proactive measures such as sustainable nursery management, integrated approaches and cluster-based frameworks are recommended to enhance early intervention and risk mitigation to protect crop and achieve sustainability. These insights offer a foundation for developing targeted strategies to improve crop resilience and productivity in regions facing similar challenges.